PowerPoint as a Learning Media for English in Islamic Boarding Schools - Bulqis, Salsabil Amalia; Alfisuma, Meria Zakiyah; Pujiati, Tri (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
Learning media in Islamic boarding schools have not been optimally implemented for English learning, the use of interactive and interesting media is still lacking. This study aims to investigate the use of PowerPoint as a medium for English learning in Islamic boarding schools. This study was conducted in one of the Islamic boarding schools in Bangkalan involving representatives of 5 science and social studies students, using a qualitative descriptive approach, data were collected through semi-structured interviews with five selected students and classroom observations. The findings of the study revealed that the integration of multimedia elements, such as videos and interactive games in PowerPoint presentations, significantly increased student interest and participation during learning. This study highlights that PowerPoint facilitates clear and concise presentation of materials, allowing students to focus on important concepts without excessive text. Ultimately, this study concludes that PowerPoint serves as an effective teaching tool that enriches the learning experience in an Islamic boarding school educational environment with Islamic values.